Protein Kinase A Regulatory Subunits in Colon Cancer - Chris C. Carlson (Neoplasia: An International Journal for Oncology Research, 1999)
The protein kinase A (PKA) is classified as type I or II depending on the association of the catalytic subunit with either the RI or RII regulatory subunits. Alterations in the levels of these regulatory subunits and PKA activity itself appear to affect cellular proliferation and tumorigenesis. We examined colorectal tumor specimens from 45 patients to investigate the potential role of cAMP-related signaling molecules in regulating tumorigenesis. Western blot analysis (PKA subunit protein levels) and in vitro kemptide phosphorylation assays (PKA catalytic subunit activity) were performed on human colorectal tumor tissue homogenates. RIα protein levels were decreased 200% in ascending and 50% in descending colonic tumors compared to adjacent mucosa. RII protein levels were decreased 77% in descending colonic tumors but no change was observed in ascending colonic tumors compared to adjacent mucosa. PKA activity and the absolute amount of catalytic subunit protein in ascending and descending tumors were unchanged compared to adjacent mucosa. Differences in cAMP-related signaling molecules exist between neoplastic and normal colorectal tissues. These differences may not only serve as potential therapeutic targets for chemotherapeutic agents, but also lead to the identification of novel regulatory mechanisms involved in cellular proliferation and tumorigenesis.